Human trampling disturbance exerts different ecological effects at contrasting elevational range limits. Issue 6 (5th April 2019) - Chardon, Nathalie Isabelle; Rixen, Christian; Wipf, Sonja; Doak, Daniel Forest
Abstract: Shifts in species geographic distributions in response to climate change have spurred numerous studies to determine which abiotic (e.g. climatic) and, less commonly, biotic (e.g. competitive) processes determine range limits. However, the impact of disturbances on range limits and their interactions with climatic and biotic effects is not well understood, despite their potential to alter competitive relationships between species or override climatic effects. Disturbance might have differential effects at contrasting range limits, based on Darwin's theory that biotic interactions set abiotically benign range limits and abiotic factors set abiotically stressful range limits. We predicted that plants at lower elevation (abiotically benign) range limits experience a net positive effect of disturbance, whereas those at higher elevation (abiotically stressful) range limits experience a net neutral effect. We examined plant populations along elevational gradients in the Colorado Rocky Mountains, in order to quantify the effects of human trampling disturbance at lower and upper elevational range limits of the common alpine cushion plants Silene acaulis and Minuartia obtusiloba . Our results are consistent with Darwin's theory. A disturbance‐mediated reduction of competitive effects increases the performance of cushion plants at lower elevations, suggesting a range limit set by biotic factors. At higher elevations, where biotic interactions are minimal, disturbance has neutral or negative effects on cushion plants. Synthesis and applications . Human trampling disturbance exerts differential effects on alpine cushion plant populations at contrasting range limits, emphasizing the need to account for the effects of climate change into the management and conservation of disturbed areas. Disturbance can diminish plant–plant competitive interactions at lower elevational range limits, and thus possibly stabilize alpine species populations susceptible to climate change‐mediated encroachment by lower elevation species. Conservation and management approaches should therefore particularly account for the differential effects of disturbance across climatic gradients. Abstract : Human trampling disturbance exerts differential effects on alpine cushion plant populations at contrasting range limits, emphasizing the need to account for the effects of climate change into the management and conservation of disturbed areas. Disturbance can diminish plant–plant competitive interactions at lower elevational range limits, and thus possibly stabilize alpine species populations susceptible to climate change‐mediated encroachment by lower elevation species. Conservation and management approaches should therefore particularly account for the differential effects of disturbance across climatic gradients.